European Union digital single market: Legal framework and challenges - Beatrice Bertarini (FrancoAngeli, 2023)
This study analyzes the evolution of the legal framework of the Digital Single Market in Europe, beginning with the first acts issued by the European Union on the subject of an information society. The gradual evolution of multiple regulatory frameworks aimed at aspects of digital technologies highlights how public regulation is now reaching the definition of the guiding principles for the Digital Single Market: in the digital era, this will increasingly dominate the lives of enterprises and citizens.
Keywords: 330